Some hysteresis tests on iron - Shepherd, G. R. (My University, 1902)
Introduction: From curves which have been drawn to show the effect of cyclic magnetizing processes in iron and in other metals, there appears one feature which is common to all; a tendency on the part of the metal to retain any magnetic condition which it may have acquired. This tendency becomes quite apparent whenever a change is made in the character of the magnetizing process. When, for instance the magnetizing force has been increased through an appreciable change of value and then is decreased through the same range in value, we find that the magnetism which was acquired by the metal is not decreased at the same rate at which it was acquired. This reluctance, on the part of the metal, to change its magnetic condition is the same when, after the magnetizing force has been wholly or partly withdrawn, it is again increased. The state of magnetization, whether the iron is fully or only partly magnetized, makes no difference in the reluctance to change the condition when the magnetizing force is changed. For instance, in the case where the current has been reversed and the magnetism wholly withdrawn, the iron is then in an apparently neutral condition, but it will be found when upon applying the current in the former direction that the iron is not susceptible of the same magnetic changes that it would be were it in the neutral state, but it acts the same as when it still retained some of its magnetism.
Citation: Shepherd, G. R. Some hysteresis tests on iron. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Iron; Hysteresis Tests; Metalurgy; Magnetism; Theses